Pengaruh Upah Dan Lingkungan Kerja Terhadap Kinerja Karyawan Di PT Indokom Samudra Persada - Novitania, Anggis; Ariningrum, Hardini; Alansori, Apip; Mulyadi, - (Jurnal Riset Akuntansi dan Manajemen Malahayati (JRAMM), 2025)
Employee performance is very important for the progress of a company. Wages and work environment are believed to be able to influence employee performance in achieving the set goals. The higher the wages and the good and pleasant work environment, the higher the employee's performance.This study aims to determine whether wages and work environment have a direct significant effect on employee performance. The population in this study were 30 employees at PT Indokom Samudra Persada. Data collected by questionnaire technique. The data analysis technique used is Multiple Linear Regression Analysis using the SPSS version 29 program.The results of this partial test indicate that wages have no significant effect, and work environment has a significant effect on employee performance. While the results of the simultaneous test show that wages and work environment have a significant effect on employee performance at PT Indokom Samudra Persada.